Implementasi Sistem Akuntansi berbasis Excel pada Kamayel Premium Wash - Budi Harsono; Vivian Carolina (INDO PUBLISHING, 2026)
Kamayel Premium Wash is an MSME that used to manually record accounting and prepare financial reports. However, Kamayel Premium Wash no longer records cash inflows and outflows or prepares financial reports. The coronavirus pandemic, which caused a decline in sales, caused Kamayel Premium Wash to experience a drastic drop in turnover. Kamayel Premium Wash finally eliminated employees working there to reduce the burden of salaries that must be paid to employees and also stopped stocking goods. With no salary payments and no inventory collection, Sugeng Santoso, the owner, also stopped preparing financial reports. Currently, the profits and losses received by Kamayel Premium Wash and the expenses incurred are also unknown in detail. After the author conducted an interview with Sugeng Santoso and learned the information, the author then created a system using the Microsoft Excel application that aims to help Sugeng Santoso to create financial reports and determine the profits or losses he earned easily. For the next PkM who conduct research, the author also recommends that this system can be refined and developed further according to the economic conditions and the needs of MSMEs (Micro, Small and Medium Enterprises) in the future.